Incremental returns from rice cultivation through gender sensitive approaches - a vivid illustration - Das, Lipi; Mondal, Biswajit; Mishra, S K; Sadangi, B N (ORYZA-An International Journal of Rice, 2021)
In addition to several household chores, women in rural areas remain involved very actively in farming activities. On getting similar access to productive resources as men, women can boost overall agricultural output as wellas income significantly. A group of farm women from 'Sankilo' village of Cuttack district, Odisha have been provided with half-an acre land with the power to decide all farm operations and ICAR-NRRI, Cuttack provided technical support for five years' period. It is being observed that returns from rice cultivation increased considerably and 'technology' in terms of demonstrations mostly contributed the difference in yield and returns over pre-project situations. Household income of family of individual women was also assessed and observed that education, family size and irrigated land holding determine the variations in income. The study advocated for appropriate policies to extend access of farm resources and impart proper education as well as capacitybuilding of the women for enhancing the knowledge and adoptive capacity for the technologies to boost the yield and income.